(untitled) (UNED Research Journal, 2018)
Recognition of peatlands as an essential part of global wetland resources has increased in recent years. Roughly half of the world’s wetlands are peatlands and are particularly vulnerable to human activities and climate change. We present the first a biophysical description of vegetation, micro relief and water of peat bogs in Macizo de la Muerte National Park, Costa Rica. Three field transects, and LANDSAT 8 images, indicate that bogs differ in water table trends and vegetation. One bog had a central flooded area dominated by Sphagnum spp.; a transitional sector with Puya dasylirioides, Blechnum buchtienii and Chusquea subtessellata; and a shrub layer dominated by Pernettya prostrata and Vaccinium consanguineum. Most trees were Quercus seemanni and Drymis granadensis. Another bog was characterized by Puya dasylirioides, Blechnum buchtienii and the aquatic herbs Paepalanthus costaricensis and Hypericum strictum, trees included Quercus seemannii and Drymis granadensis (at the edges of the wetland). The progressive reduction of water in wetlands represents a risk of degradation and transformation of bogs into another type of ecosystem